2006
DOI: 10.1128/jcm.44.2.628-631.2006
|View full text |Cite
|
Sign up to set email alerts
|

Sonication of Explanted Prosthetic Components in Bags for Diagnosis of Prosthetic Joint Infection Is Associated with Risk of Contamination

Abstract: Explanted orthopedic implants from 54 patients with aseptic failure and 24 patients with prosthetic knee or hip infection were sonicated in polyethylene bags. The sensitivities of periprosthetic tissue and sonicate fluid cultures for the diagnosis of prosthetic joint infection were 54% and 75%, whereas the specificities were 98% and 87%, respectively. Sonication in bags improved bacterial recovery from the surface of orthopedic implants; however, it lacked specificity, due to bag leakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
156
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(163 citation statements)
references
References 12 publications
3
156
0
4
Order By: Relevance
“…There were 17 patients allocated to the infection group. The criteria for inclusion in this group were a positive peri-prosthetic tissue culture obtained during the revision surgery or open biopsy of the hip, acute inflammation as seen on histological examination by a clinical pathologist (TH) of either frozen sections of peri-prosthetic tissue, or fixed tissues, and visibly purulent synovial fluid in the joint or the area surrounding the prosthesis, according to the criteria of Trampuz et al 3 The noninfection group comprised 29 patients, in whom none of the diagnostic criteria for infection were present, and who had no more than five neutrophils in any high-powered field on frozen section. 4 Of the 17 patients in the infection group, there were ten men and seven women, with a mean age at operation of 57 years (38 to 78).…”
Section: Methodsmentioning
confidence: 99%
“…There were 17 patients allocated to the infection group. The criteria for inclusion in this group were a positive peri-prosthetic tissue culture obtained during the revision surgery or open biopsy of the hip, acute inflammation as seen on histological examination by a clinical pathologist (TH) of either frozen sections of peri-prosthetic tissue, or fixed tissues, and visibly purulent synovial fluid in the joint or the area surrounding the prosthesis, according to the criteria of Trampuz et al 3 The noninfection group comprised 29 patients, in whom none of the diagnostic criteria for infection were present, and who had no more than five neutrophils in any high-powered field on frozen section. 4 Of the 17 patients in the infection group, there were ten men and seven women, with a mean age at operation of 57 years (38 to 78).…”
Section: Methodsmentioning
confidence: 99%
“…They resumed a high sensitivity but a lack of specificity because the infected prostheses were sonicated in leaking plastic bags. 21 Using sterile containers instead of plastic bags and adding a vortexing step before sonication they modified this method resulting in a higher sensitivity of SC than that of the periprosthetic TC (78.5% vs. 60.8%, p < 0.001). 22 Piper et al 23 also reported a significant difference between SC and periprosthetic TCs (66.7% vs. 54.5%, p ¼ 0.046) for the detection of definite prosthetic shoulder infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sensitivities (range, 0.67 to 0.91) and specificities (range, 0.72 to 1.0) among studies assessing the diagnostic value of SFC for PJI are inconsistent (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The Infectious Diseases Society of America guidelines suggest a gap in the validation of the diagnostic value of SFC for PJI and request additional higher-level evidence (8).…”
mentioning
confidence: 99%
“…Further, various factors, including antibiotic use and specimen contamination, may influence the diagnostic ability of SFC (12,14,16,17). We identified 120 false-negative results from 12 studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation